2016
DOI: 10.1161/circresaha.116.307308
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Acute Inflammation and the Role of Resolvins in Immunity, Thrombosis, and Vascular Biology

Abstract: Acute inflammation is a host-protective response that is mounted in response to tissue injury and infection. Initiated and perpetuated by exogenous and endogenous mediators, acute inflammation must be resolved for tissue repair to proceed and for homeostasis to be restored. Resolution of inflammation is an actively regulated process governed by an array of mediators as diverse as those that initiate inflammation. Among these, resolvins have emerged as a genus of evolutionarily conserved pro-resolving mediators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(112 citation statements)
references
References 181 publications
(286 reference statements)
2
108
0
2
Order By: Relevance
“…An increase in the gene expression of Alox5ap 24 hrs following FUS may contribute to the resolution of inflammation by affecting the activity of 5-lox and subsequently the production of lipoxins and resolvins39. Additionally, increased expression of Timp1 has been found to attenuate inflammation in endothelium;40 Lyz2 has been implicated in reduction of Il1β, Il6, Tnfα, and Ccl2 production in human ECs;41 Slamf7 has been shown to inhibit the production of proinflammatory cytokines42.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the gene expression of Alox5ap 24 hrs following FUS may contribute to the resolution of inflammation by affecting the activity of 5-lox and subsequently the production of lipoxins and resolvins39. Additionally, increased expression of Timp1 has been found to attenuate inflammation in endothelium;40 Lyz2 has been implicated in reduction of Il1β, Il6, Tnfα, and Ccl2 production in human ECs;41 Slamf7 has been shown to inhibit the production of proinflammatory cytokines42.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our results suggest a potential physiologic mechanism by which coagulation initiates the endogenous production of functional n-3-derived SPMs that affect innate immune cells. Because the physiologic coagulation of blood is protective in humans, SPM production by clots may be of direct relevance to pathophysiology events in surgery (41), infection (11, 27, 42, 43), vascular inflammation (44, 45), stroke, and cancer (46, 47). …”
Section: Discussionmentioning
confidence: 99%
“…The paradigm for an acute inflammatory response can now be viewed as consisting of 2 stages: initiation (productive and transition phases) and resolution . Traditionally, there has been a view that excess inflammatory mediator production underlies chronic inflammation, but, increasingly, evidence shows that disruptions in production of endogenous SPMs may be at least as equally important, as they not only actively terminate the production of inflammatory mediators but also directly stimulate macrophage phagocytosis of both apoptotic cells and bacteria, promote egress of phagocytes from sites of inflammation, regulate polymorphonuclear neutrophil (PMN) apoptosis, promote chemokine scavenging, and stimulate tissue repair and regeneration . Thus, SPMs have been shown to improve outcomes in many cell‐ and animal‐based models, limiting neutrophilic infiltration and enhancing macrophage resolution responses, and, consequently, may have an important role in conditions characterized by excessive, uncontrolled inflammation .…”
Section: Focus On Lipid Emulsions Containing Fish Oilmentioning
confidence: 99%
“…Thus, SPMs have been shown to improve outcomes in many cell‐ and animal‐based models, limiting neutrophilic infiltration and enhancing macrophage resolution responses, and, consequently, may have an important role in conditions characterized by excessive, uncontrolled inflammation . It is also important to note that some chronic inflammatory diseases are associated with defects in production of SPMs . Furthermore, administration of DHA or EPA increases resolvin production in animal models of inflammation, and human studies have shown that ω‐3 PUFA intake increases the concentration of resolvins and their biosynthetic pathway markers in plasma or serum .…”
Section: Focus On Lipid Emulsions Containing Fish Oilmentioning
confidence: 99%